Effects of stress and burnout on librarians in selected academic libraries in Metro Manila - Caguiat, Cynthia A.; Santos, Herminia H.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
The study focused on the effects of stress and burnout on librarians in selected academic libraries in Metro Manila. It was conducted to: (1) determine the level of burnout; (2) identify the sources of job-related stress; (3) determine manifestations fo stress; (4) describe the level of burnout which affect job performance in relation to the following personal and professional characteristics, such as, civil status, age, educational attainment, position/designation in the library, and length of employment in the library; and (5) identify the individual coping mechanisms and stress reduction techniques provided by their organizations.
Respondents were academic librarians from seven institutions of higher learning located in Metro Manila, namely, Ateneo de Manila University (ADMU), De La Salle University (DLSU), Far Eastern University (FEU)-Manila, Pamantasan ng Maynila, University of Santo Tomas (UST), University of the East (UE)-Manila, and University of the Philippines-Diliman (UPD). A survey questionnaire was the main research instrument in the study. Two hundred questionnaires were sent to academic librarians; 170 were returned; 169 were valid for the study.
A big fraction of respondents are working in the reference and information service, circulation service and computer related activities, findings indicate stress appears more prevalent in this type of library work.
When it comes to the level of burnout, the biggest percentage of the responses fall under the very mild emotional exhaustion level. This shows that using the MBI, the academic librarians are not emotionally exhausted. Most of the academic librarians feel that "they are working too hard for the job." Only a small percentage of the respondents under study feel strongly that they are "frustrated with their work." Respondents as a whole experienced a very mild depersonalization level which indicates that academic librarians "do not really feel negative, cynical and callous attitudes towards their clients." Personal accomplishment is strong for the study. One aspect of personal accomplishment strongly felt by the librarians are "feeling of happiness after working closely with clients."
The most common organizational stressors, having the most response on always category, are "low budget." "Low budget" pertains to insufficient funding, which includes inadequate information sources, facilities and equipment, staff shortages and turnover rates that are a possible cause of burnout among academic librarians. However, organizational stressors do not really affect the librarians under study. The job stressor, which most contributes stress to the librarians, is "overworked." This factor includes working beyond the job description, conflicting job task and demands, and work overload. Another factor, which contributes significantly to stress of academic librarians, are "low advancement and working conditions." Overall, the job and career stressors do not really contribute a large amount of stress to the academic librarians.
The most common manifestations of stress frequently experienced by the librarians under study were "backaches" and "headaches" with the highest responses on always column. The indication of burnout frequently encountered by the respondents is mostly related to their physical well being.
With regards to their job performance (for the last six months), the respondents think that their overall function as librarian was excellent. No one declared that their performance had deteriorated. Based on the study, the most common or the top individual coping mechanisms employed by the academic librarians are: "to look for ways to make the work more interesting," "set priorities and deal with the problems accordingly," "deliberately separate home and work," and "plan ahead." Most responses are towards the positive way of coping stress rather than the negative way such as smoking, drinking alcohol, use of tranquilizers and sedatives. The most common stress reduction techniques and remedies given to the librarians by the organizations are "skill training programs," followed by "breaks during work," then "orientation programs," "improve working conditions," and "improve communications."
The most common stress management techniques used by the librarians who attended stress management programs are "physical exercise," "deep breathing," and "progressive relaxation techniques." Respondents who tried to attend stress management programs claims that it has been very helpful in reducing stress.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries--Philippines--Manila Metropolitan Area; Burn out (Psychology).; College librarians--Philippines--Manila Metropolitan Area--Job stress; Stress (Psychology).